Comparative analysis of oral and intraperitoneal glucose tolerance tests in mice - Lewin Small; Amy Ehrlich; Jo Iversen; Stephen P. Ashcroft; Kajetan Trošt; Thomas Moritz; Bolette Hartmann; Jens J. Holst; Jonas T. Treebak; Juleen R. Zierath; Romain Barrès (Elsevier, 2022)
Objective: The glucose tolerance test (GTT) is widely used in preclinical research to investigate glucose metabolism, but there is no standardised way to administer glucose. The aim of this study was to directly compare the effect of the route of glucose administration on glucose and insulin kinetics during a GTT in mice. Methods: A GTT was performed in lean male and female mice and obese male mice and glucose was administered via the oral or intraperitoneal (I.P.) route. Samples were collected frequently during the GTT to provide a full time-course of the insulin and glucose excursions. In another cohort of lean male mice, plasma concentrations of insulin, c-peptide, and incretin hormones were measured at early time points after glucose administration. A stable-isotope labelled GTT (SiGTT) was then performed to delineate the contribution of exogenous and endogenous glucose to glycemia during the GTT, comparing both methods of glucose administration. Finally, we present a method to easily measure insulin from small volumes of blood during a GTT by directly assaying whole-blood insulin using ELISA and show a good concordance between whole-blood and plasma insulin measurements. Results: We report that I.P. glucose administration results in an elevated blood glucose excursion and a largely absent elevation in blood insulin and plasma incretin hormones when compared to oral administration. Utilising stable-isotope labelled glucose, we demonstrate that the difference in glucose excursion between the two routes of administration is mainly due to the lack of suppression of glucose production in I.P. injected mice. Additionally, rates of exogenous glucose appearance into circulation were different between lean and obese mice after I.P., but not after oral glucose administration. Conclusion: Reflecting on these data, we suggest that careful consideration be given to the route of glucose administration when planning a GTT procedure in mice and that in most circumstances the oral route of glucose administration should be preferred over the I.P. route to avoid possible artifacts originating from a non-physiological route.